IMPLEMENTASI KEBIJAKAN UJI KOMPETENSI LULUSAN MAHASISWA BIDANG KESEHATAN DI REGIONAL IV WILAYAH PROVINSI SULAWESI SELATAN DAN SULAWESI TENGGARA - Gunarmi Gunarmi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2018)
Health workers human resources is a milestone in the success of health services. Recognition of graduate competence is competence certificate by act No. 12 of 2012. Health workers human resources have been complete national competence test obtained competence certificate which is consitute of quality skill grade for further training and guarantee the school of health science graduate. Regulation No. 12 of 2016; determine supplementary factor and inhibiting factor in national competence test implementation; and create the policy model of national competence test implementation in guarantee of health student. Design of research used qualitative descriptive approach. The respondent is school of health science in Makasar region. The primary data collected through interview, observation, and documentation. Data analysis used qualitative data analysis. Result of this research is : 1) Implementation of competence certificate policy which refers to ministerial of high school regulation No. 12 of 2016 inconsistent with mandate of act No. 12 of 2012 about high school, act No. 36 of 2014 about health workers, and ministerial of high school regulation No. 44 of 2014 about high school national standard. 2) Supplement factor of implementation competence certificate policy is the enachment of competence certificate policy in form ministerial of high school regulation, therefore must be implementing appropriate by the policy. While inhibiting factor of implementation competence certificate policy is refers to variable of Van Meter and Van Horn theory that showed low policy performance, therefore involved on disparity quality of learning has an impact on rate of re-taker increase. 3) Models of competence certificate policy which is still being centralistic implemented, therefore necessary to reconstruct competence certificate policy by exit-exam models with principle of integrated, synergistic, transparent, controlled, and accountable.